Efektivitas Pelatihan Literasi Digital Dalam Meningkatkan Kompetensi Masyarakat Di Rt 16 Jalan Sepakat 3 Sawah Lebar Baru - Agung, Rizki Defa; Intania, Felly; Lisniarti, Henni; Nabila, Filza Ratu; Jayadi, Agung; Hasti, Pra (LPPM Universitas Dehasen Bengkulu, 2026)
The Dehasen University Bengkulu Thematic Community Service Program, in collaboration with BPPTIK Kominfo, conducted digital literacy training based on seven HP LIFE and Cisco modules for the community in RT 16, Jalan Sepakat 3, Kelurahan Sawah Lebar Baru. This activity was motivated by the low level of digital awareness among the community, characterized by a lack of understanding of basic technology, low confidence in the use of digital devices, and limited access to technology-based information. This study aims to analyze the effectiveness of training in improving the basic competencies of the community, particularly in terms of knowledge, device usage skills, and changes in attitudes towards technology. The research used a qualitative descriptive approach with data collection techniques in the form of observations during training, interviews with participants, and documentation of activities in each module. Data analysis was carried out through data reduction, data presentation, and thematic conclusions. The results showed that HP LIFE and Cisco module-based training had a positive impact on improving the community's digital literacy. Participants who initially showed resistance and distrust of technology began to understand the basic benefits of digital devices, were able to operate simple features, and showed interest in continuing independent learning. Factors supporting the effectiveness of the training included applicable delivery methods, intensive mentoring, and the relevance of the material to daily needs. However, infrastructure limitations and differences in education levels posed challenges that required further strategies. Overall, this training has proven effective in improving the basic digital literacy competencies of rural communities and has made a real contribution to efforts to strengthen digital capacity in the local environment.